Diseño e implementación de un banco de prueba de cargas eléctricas residenciales (2021)
During the development of this project, the design and construction of a test bench for residential electrical loads was carried out as an educational tool to support teachers and students in the study of the operation of electrical systems and residential installations through the realization of practices. experimental; all this according to the technical guidelines of the Colombian Electrical Code -